Isolated cardiac tamponade following blunt trauma in an infant - Philip Maykowski, MPH; Jae-O. Bae, MD; David M. Notrica, MD (Elsevier, 2019)
This is a case of a 6-month old female with no prior medical history who presented to the emergency department following a high-speed motor collision with ejection of an improperly installed car seat. The patient was hemodynamically unstable with tachycardia, poor perfusion, and marks from the car seat. A focused assessment with sonography in trauma (FAST) ultrasound exam revealed no intraabdominal fluid, but evidence of cardiac tamponade which was confirmed by chest CT angiography. No cardiac or great vessel injury was present. A pericardial window was performed using a subxiphoid approach and 150 mLs of blood was drained resulting in immediate hemodynamic stabilization. The patient continued to improve from a cardiac stand point but her hospital course was complicated by iatrogenic right arm ischemia due to arterial line attempt. The patient was discharged after a 12-day hospital stay. Keywords: Cardiac tamponade, Blunt trauma, Infant